EFEKTIVITAS PERAN LEMBAGA PEMASYARAKATAN DALAM UPAYA PEMBINAAN NARAPIDANA DITINJAU DARI UNDANG-UNDANG NO. 22 TAHUN 2022 TENTANG PEMASYARAKATAN - Firman Aji Pamungkas; Muhamad Abas; Anwar Hidayat (LPPM STIH Awang Long, 2023)
Correctional Institution is a place to carry out coaching for prisoners and Correctional Students which is carried out using the correctional system. This study aims to (1) determine the effectiveness of the role of correctional institutions in the efforts to foster convicts in terms of law no. 22 of 2022 concerning correctional (2) determines the implementation of coaching in Class IIA Bekasi Penitentiary for convicts who are sentenced to light crimes. The type of research used in this research is empirical juridical with the nature of descriptive research. This research was conducted at the Bekasi Class IIA Penitentiary. The data collection technique was carried out by using interviews and literature study techniques. The data collection method was processed qualitatively. The results of the research (1) determine the effectiveness of the role of correctional institutions in the efforts to foster convicts in terms of law no. 22 of 2022 concerning correctional facilities is not yet fully effective because in reality there are still convicts who commit repeated crimes. (2) knowing that the implementation of coaching in Class IIA Bekasi Penitentiary for convicts sentenced to light crimes has not been fully implemented properly, as evidenced by the fact that the rights of prisoners have not been fully fulfilled and some activities are not running optimally due to overcapacity of correctional institutions, not in proportion to the number training officers and convicts, as well as the lack of supporting facilities and infrastructure for coaching.